Variabilidade espacial e dinâmica do acúmulo de forragem em pastos de capim-braquiária sob lotação contínua - Santos, Manoel Eduardo Rozalino (2009)
Two experiments were performed on Brachiaria decumbens cv. Basilisk (signalgrass) pastures belonging to the Setor de Forragicultura do Departamento de Zootecnia at the Universidade Federal de Viçosa. The first one was carried out between November 2007 and May 2008 aiming to quantify the spatial variability of the signalgrass pastures managed under continuous stocking with cattle. For that, four different plant heights (10, 20, 30 and 40 cm) were evaluated on the same signalgrass pasture managed to be 25 cm high, which was possible due to the natural variability of the vegetation. Randomized block design with two repetitions was used. The following variable answers were determined: temporal variation of the plant height, mass and volumetric density of the forage and its morphological components, canopy interception of light, population density and tiller characteristics, and morphogenic and structural characteristics of the pasture. The second experiment was carried out between June 2008 and March 2009. Within this period, two management strategies were evaluated. In one of them, the pasture was kept to have 25 cm in height throughout the experimental period. In the other one, the pasture was kept to have 15 cm in height during the winter, and 25 cm from the beginning of the spring on. Randomized block design with subdivided plots and 4 repetitions was used. The plots correspond to the management strategies of the pasture, and the subplots to the seasons of the year. Number of tillers, tissue flux, dynamics of tillering, and forage accumulation were quantified. In the first experiment, the temporal variation of the plant height showed negative linear response according to the signalgrass height. The masses of forage and its morphological components increased linearly while the volumetric density of the forage decreased as the plant height increased. Canopy light interception (IL) varied according to the quadratic pattern, that is, plants that were 10, 20, 30 and 40 cm high showed 56.2, 85.2, 93.4 and 96.6% of IL, respectively. The number of vegetative tillers and green tillers decreased linearly while the reproductive tillers and dead tillers increased linearly as the plant height increase. The mass of the morphological components and the weight of tillers also increased linearly according to the plant height. Regarding the morphogenic and structural characteristics of the tillers, linear effects were observed with additions on the leaf senescence rate, pseudoculm elongation rate, number of grazed leaves, and leaf blade and pseudoculm lengths, as well as a decrease on the leaf appearance rate as the plant height increased in the same pasture. In the second experiment, the lowering of the pasture to 15 cm high in the winter resulted in a higher leaf appearance rate (0.02 leaf/tiller.day) and higher number of green leaves (4.5 leaves per tiller) in the winter. However, this management strategy decreased the duration of leaf life (66 days), senescence leaf rate (0.22 cm/tiller.day), and leaf blade (11 cm) and pseudoculm (15.2 cm) lengths in the winter months, in relation to the pasture kept at 25 cm high. In this season, the rates of leaf appearance (0.06 leaf/tiller.day), leaf elongation (0.110 cm/tiller.day) and pseudoculm elongation (0.008 cm/tiller.day) were lower. The number of green leaves (2.9 leaves per tiller), and leaf blade (8.6 cm) and pseudoculm (13.5 cm) lengths were also lower. On the other hand, leaf life duration (139 days) and number of dead leaves (2.0 leaves per tiller) were higher in the winter. The highest rate of leaf senescence was found in the spring (0.40 cm/tiller.day). As to the dynamics of tillering of signalgrass, the tiller appearance rate (4.7%), the site filling (0.103 tiller/leaf), the mortality rate (4.7%) and the number of vegetative tiller (1.620 tillers/m2), they were all found to be lower in the winter. In this season, however, tiller survival rate was higher (95.3%). Throughout the seasons, the number of dead tiller was lower in the spring (490 tiller/m2), while the number of reproductive tiller was higher in the summer (244 tiller/m2). When comparing the pastures kept at 25 cm high, the ones managed to be 15 cm high in the winter showed higher rates of tiller appearance (34.2%), site filling (0.133 tiller/leaf) and number of vegetative tiller (1852 tiller/m2), besides a lower number of dead tiller (566 tiller/m2). If compared to the pasture kept as 25 cm, lowering the pasture height to 15 cm in the winter also resulted in higher rates of total growth (95 kg/ha.day) and leaf (66.1 kg/ha.day) as well as higher rates of total accumulation (81.5 kg/ha.day) and leaf (52.6 kg/ha.day). The production of accumulated forage (from the winter to the summer) was higher for the pasture lowered to be 15 cm in the winter (25.6 t/ha of dry matter) in relation to the pasture managed to be 25 cm high (22 t/ha of dry matter). When considering the seasons of the year, in the winter, there were lower rates of total growth (6.4 kg/ha.day), leaf growth (5.6 kg/ha.day) and pseudoculm growth (0.8 kg/ha.day), and also lower rates of total accumulation (-6.6 kg/ha.day) and leaf accumulation (-7.5 kg/ha.day), while a higher rate of leaf senescence (22.4 kg/ha.day) was found in the spring. Based on the results found, one may conclude that: (1) there is indeed spatial and temporal variability of the Brachiaria decumbens cv. Basilisk pastures managed under continuous stocking with cattle; (2) the structure of the pasture is modified by the height of the forage plant; (3) the forage accumulation is optimized when the signalgrass pasture is lowered to have 15 cm in height during the winter, 25 cm in the following spring and summer.